Espaces virtuels et pré-expérience de l’espace géographique - Jérémie Valentin; Fanny Georges; Yasmine Boumenir; Birgitta Dresp-Langley (Netcom)
“Virtual spaces and pre-experience in geographic space”- The virtual representations of space have largely democratized in recent years. Market liberalization of satellite images and increased capacity of data transfer on the wired and non wired deeply involved in the establishment of virtual globes now connected to cyberspace. The man has more and more use of virtual spaces for understanding space. Whether developing a route or finding a place, the paper map and tourist guide disappear in favor of Virtual Earth and mobile phones.In this context transfer usage, virtual representations of space appear, along with the use of GPS, providing a skewed perception of space. For despite their intrinsic qualities common, especially for navigation in an unknown space, their use would change our relationship to space and in some cases could affect their learning. The objective of this multidisciplinary communication is to update the popularity of virtual globes while questioning their practices in the pre-condition of spatial experience. For the current devices used to test virtual space prior to physically experience. We see through a comparative experiment, as part of a complex path, subjects who had a pre-experience of virtual space are less efficient than subjects who saw a plane 2D paper and less effective than subjects who completed a tour. Analysis of GPS traces of subjects will allow us to draw conclusions about the types of failures and errors.